Preschool Psychopathology Reported by Parents in 23 Societies: Testing the Seven-Syndrome Model of the Child Behavior Checklist for Ages 1.5-5 - Ivanova, M.; Achenbach, T.; Rescorla, L.; Harder, V.; Ang, R.; Bilenberg, N.; Bjarnadottir, G.; Capron, C.; De Pauw, S.; Dias, P.; Dobrean, A.; Doepfner, M.; et al. (Elsevier BV, 2010)
Journal Home Register or Login: Password: Auto-Login [Reminder]Search forAdvanced Search - MEDLINE - My Recent Searches - My Saved Searches - Search TipsJOURNAL HOMECURRENT ISSUEEDICIÓN ESPAÑOLAARTICLES IN PRESSFORTHCOMING CONTENTSEARCH THIS JOURNALBROWSE ALL ISSUESCOLLECTIONSCMEPODCASTSPRESS RELEASESJOURNAL INFORMATION• Aims and Scope• Editorial Board• Author Information• Info for Advertisers• Contact Information• Permission to Reuse• Pricing InformationONLINE SUBMISSIONSSUBSCRIBE TO JOURNALCAREER OPPORTUNITIESCHILD AND ADOLESCENT PSYCHIATRIC CLINICS OF NORTH AMERICAPSYCHIATRIC CLINICS OF NORTH AMERICAABSTRACTING/INDEXINGRSS RSSMore periodicals:FIND A PERIODICALFIND A PORTALGO TO PRODUCT CATALOG Volume 49, Issue 12, Pages 1215-1224 (December 2010) View previous. 10 of 26 View next.ABSTRACTFULL TEXTFULL-TEXT PDF (474 KB)GET FULL TEXT ELSEWHERECITATION ALERTCITED BYRELATED ARTICLESEXPORT CITATIONEMAIL TO A COLLEAGUE[High-quality image available] DOWNLOAD IMAGESNEED REPRINTS?BOOKMARK ARTICLEPreschool Psychopathology Reported by Parents in 23 Societies: Testing the Seven-Syndrome Model of the Child Behavior Checklist for Ages 1.5–5Masha Y. Ivanova, Ph.D.1Corresponding Author Informationemail address, Thomas M. Achenbach, Ph.D.1, Leslie A. Rescorla, Ph.D.2, Valerie S. Harder, Ph.D.1, Rebecca P. Ang, Ph.D.3, Niels Bilenberg, M.D., Ph.D.4, Gudrun Bjarnadottir, Ph.D.5, Christiane Capron, Ph.D.6, Sarah S.W. De Pauw, M.A.7, Pedro Dias, Ph.D.8, Anca Dobrean, Ph.D.9, Manfred Doepfner, Ph.D.10, Michele Duyme, Ph.D.6, Valsamma Eapen, Ph.D.11, Nese Erol, Ph.D.12, Elaheh Mohammad Esmaeili, Ph.D.13, Lourdes Ezpeleta, Ph.D.14, Alessandra Frigerio, Ph.D.15, Miguel M. Gonçalves, Ph.D.16, Halldor S. Gudmundsson, M.A.17, Suh-Fang Jeng, Sc.D.18, Pranvera Jetishi, B.A.26, Roma Jusiene, Ph.D.19, Young-Ah Kim, Ph.D.20, Solvejg Kristensen, M.H.Sc.4, Felipe Lecannelier, M.A.21, Patrick W.L. Leung, Ph.D.22, Jianghong Liu, Ph.D.23, Rosario Montirosso, M.Sc.15, Kyung Ja Oh, Ph.D.24, Julia Plueck, Ph.D.10, Rolando Pomalima, M.D.25, Mimoza Shahini, M.D.27, Jaime R. Silva, Ph.D.28, Zynep Simsek, Ph.D.29, Andre Sourander, M.D.30, Jose Valverde, M.D.25, Karla G. Van Leeuwen, Ph.D.31, Bernardine S.C. Woo, M.Med.32, Yen-Tzu Wu, M.S.18, Stephen R. Zubrick, Ph.D.33, Frank C. Verhulst, M.D., Ph.D.34Accepted 28 September 2010. published online 12 November 2010.ObjectiveTo test the fit of a seven-syndrome model to ratings of preschoolers' problems by parents in very diverse societies.MethodParents of 19,106 children 18 to 71 months of age from 23 societies in Asia, Australasia, Europe, the Middle East, and South America completed the Child Behavior Checklist for Ages 1.5–5 (CBCL/1.5–5). Confirmatory factor analyses were used to test the seven-syndrome model separately for each society.ResultsThe primary model fit index, the root mean square error of approximation (RMSEA), indicated acceptable to good fit for each society. Although a six-syndrome model combining the Emotionally Reactive and Anxious/Depressed syndromes also fit the data for nine societies, it fit less well than the seven-syndrome model for seven of the nine societies. Other fit indices yielded less consistent results than the RMSEA.ConclusionsThe seven-syndrome model provides one way to capture patterns of children's problems that are manifested in ratings by parents from many societies. Clinicians working with preschoolers from these societies can thus assess and describe parents' ratings of behavioral, emotional, and social problems in terms of the seven syndromes. The results illustrate possibilities for culture–general taxonomic constructs of preschool psychopathology. Problems not captured by the CBCL/1.5–5 may form additional syndromes, and other syndrome models may also fit the data.Key Words: preschoolers, assessment, taxonomy, multicultural, confirmatory factor analysis1 University of Vermont2 Bryn Mawr College3 Nanyang Technological University4 University of Southern Denmark5 Glaesibaer Health Clinic6 University of Paris7 Ghent University8 Portugese Catholic University9 Babes-Bolyai University10 University of Cologne11 University of New South Wales12 Ankara University13 Institute for Exceptional Children14 Universitat Autonoma de Barcelona15 Scientific Institute E. Medea16 University of Minho17 University of Iceland18 National Taiwan University26 University of Dardania19 Vilnius University20 Hunoconsulting21 Universidad del Desarrollo22 Chinese University of Hong Kong23 University of Pennsylvania24 Yonsei University25 Peruvian National Institute of Mental Health27 University Clinical Center of Kosova28 Universidad de La Frontera29 Harran University30 Turku University and Turku University Hospital31 Leuven University32 Child Guidance Clinic of the Singapore Institute of Mental Health33 Curtin Centre for Developmental Research, Curtin University of Technology34 Erasmus University Medical Center-Sophia's Children's HospitalCorresponding Author InformationCorrespondence to: Masha Y. Ivanova, Ph.D., Vermont Center for Children, Youth and Families, University of Vermont, 1 South Prospect Street, Burlington, VT 05401 This article is discussed in an editorial by Dr. Alice Carter on page 1181. Disclosure: Dr. Ivanova receives research and salary support from the Research Center for Children, Youth, and Families, which publishes the Child Behavior Checklist (CBCL). Dr. Achenbach is President of the Research Center for Children, Youth, and Families, and receives remuneration. Dr. Rescorla receives remuneration from the Research Center for Children, Youth, and Families. Dr. Harder previously held a University of Vermont Postdoctoral Fellowship funding by the Research Center for Children, Youth, and Families. Drs. Bjarnadottir, Gudmundsson, Leung, Verhulst, and Mr. Gudmundsson, receive research support from the sale of the CBCL. Dr. Bilenberg has received honoraria from Eli Lilly and Co., Novartis, Neuroscience, and Janseen Cilag. He has received research support from the Danish Research Foundation, the Lundbeck Foundation, Hermansens Mindelegat, and Mads Clausen Fond. Dr. Eapen has received research support from the Sheikh Hamdan Bin Rashid Al Maktoum Award for Medical Sciences. Dr. Jusiene has received research support from the Lithuanian Science and Studies Foundation. Drs. Ang, Capron, Dias, Dobrean, Doepfner, Duyme, Erol, Esmaeili, Ezpeleta, Frigerio, Gonçalves, Jeng, Kim, Liu, Oh, Plueck, Pomalima, Shahini, Silva, Simsek, Sourander, Valverde, Van Leeuwen, and Zubrick, Ms. De Pauw, Ms. Kristensen, Mr. Lecannelier, Ms. Montirosso, Ms. Jetishi, Ms. Woo, and Ms. Wu report no biomedical financial interests or potential conflicts of interest.PII: S0890-8567(10)00735-5doi:10.1016/j.jaac.2010.08.019© 2010 American Academy of Child and Adolescent Psychiatry. Published by Elsevier Inc. All rights reserved. View previous. 10 of 26 View next. Copyright © 2011 Elsevier, Inc. All rights reserved | Privacy Policy | Terms & Conditions | Feedback | About Us | Help | Contact Us |The content on this site is intended for health professionals.